Oligometastatic Disease and Interventional Oncology: Rationale and Research Directions. Issue 2 (March 2020) - Murali, Nikitha; Ludwig, Johannes M.; Nezami, Nariman; Kim, Hyun S.
Abstract : Abstract: Oligometastatic disease (OMD) is generally defined as a stage of clinically or radiographically demonstrated metastatic disease limited in total disease burden and without rapid spread. Interventional oncology performs local therapies for primary and metastatic cancers, including OMD. Interventional oncology treatments can be pursued both as definitive therapy and for palliative purposes. Applied to OMD, these interventions can offer patients a decreasing overall tumor burden, minimizing cancer morbidity, and early evidence suggests a survival benefit. Here, we discuss the range of interventional oncology treatments, including ablation, chemoembolization, radioembolization, and irreversible electroporation. We describe the rationale for their application to OMD and discuss future directions for research.